2007
DOI: 10.1107/s0021889807040149
|View full text |Cite
|
Sign up to set email alerts
|

On the precision and accuracy of structural analysis of light-induced metastable states

Abstract: International audienceAbstract: Bragg diffraction data were collected on single crystals of the spin-crossover complex [Fe(phen)2(NCS)2] in its low-spin and light-induced metastable high-spin states. Experimental variables included the temperature (32 and 15 K), the X-ray source (sealed tube and synchrotron), and the time interval between laser light excitation of the sample ([lambda] = 647 nm). From a comparison of the structural parameters refined, it is shown that photo-crystallographic measurements suffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 56 publications
7
41
0
Order By: Relevance
“…It undergoes an abrupt and complete transition from the S = 2 HS state to the S = 0 LS state when the temperature is decreased below the transition temperature T 1/2 ≈ 176 K. The attention this complex has attracted is also due to the fact that it was the first SCO complex for which the crystal structure was available for the HS and for the LS phase [48]. A more recent study by Legrand et al [49] presents the crystal structure of the LS and of the (metastable) HS phase at 15 K. Fe(phen) 2 (NCS) 2 crystallizes in the space group Pbcn, with four complexes in the unit cell. At 15 K the volume of the unit cell increases by about 61.3 Å 3 upon transition from the LS to the HS phase which corresponds to an increase of 2.8%, a typical value for the volume expansion upon spin crossover [1].…”
Section: Introductionmentioning
confidence: 99%
“…It undergoes an abrupt and complete transition from the S = 2 HS state to the S = 0 LS state when the temperature is decreased below the transition temperature T 1/2 ≈ 176 K. The attention this complex has attracted is also due to the fact that it was the first SCO complex for which the crystal structure was available for the HS and for the LS phase [48]. A more recent study by Legrand et al [49] presents the crystal structure of the LS and of the (metastable) HS phase at 15 K. Fe(phen) 2 (NCS) 2 crystallizes in the space group Pbcn, with four complexes in the unit cell. At 15 K the volume of the unit cell increases by about 61.3 Å 3 upon transition from the LS to the HS phase which corresponds to an increase of 2.8%, a typical value for the volume expansion upon spin crossover [1].…”
Section: Introductionmentioning
confidence: 99%
“…It certainly is one of the most intensively studied SCO complex and also one of the very few that have been studied by periodic DFT calculations [12,[19][20][21][22][23][24]. High precision crystal structures are available for the HS and LS phases at different temperatures down to 15 K [25,26]. An abrupt transition from a S = 0 low spin to a S = 2 high spin state has been observed at about 176 K, together with a narrow thermal hysteresis.…”
Section: Ising-like Modelsmentioning
confidence: 99%
“…with the experimental values (2219 Å 3 at 130 K and 2338 Å 3 at 293 K -measured by Gallois et al [25], 2186 Å 3 at 15 K and 2248 Å 3 at the same temperature after irradiation with light -measured by Legrand et al [26]), in contrast to previous LDA calculations, where good agreement could be reached only for the volume expansion upon spin transition [12], due to the notorious underestimation of bond lengths by LDA methods [27]. The proper choice of the Hubbard parameter U is obviously connected to the choice of the density functional.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…The success of kind experiments consists in in situ laser irradiation of a cryogenically cooled crystal, with a N2 or He gas-flow system for less restricted access than closed cryostat (White et al, 1994), mounted on a diffractometer equipped with a CCD detector for fast data collection (Graafsma et al, 1997;Muchmore, 1999). More recently, Legrand (2005) has developed a crystallographic experimental methodology approach 2007a;2007b) and shown that it is possible to measure with accuracy photo-induced metastable states and to refine its experimental electron density below 35 K using conventional X-ray sources (Legrand et al, 2006;Pillet et al, 2008).…”
Section: State-of-the-art Sample Environments At Laboratoriesmentioning
confidence: 99%